Is there an Increase in Total Hip Arthroplasty Due to Osteonecrosis of Femoral Head After Covid-19 Pandemic?: A Retrospective Study Among Patients in Central Karnataka, India - R Aishwarya; Vijayakumar S Kulambi; Subodh B Shetty; Harsh Kirthi Rao (Journal of Orthopaedic Case Reports)
Introduction: Coronavirus disease 2019 (COVID-19) infection or corticosteroid usage during the COVID-19 pandemic as risk factors for avascular necrosis (AVN) of the femoral head (osteonecrosis of the femoral head/femoral head AVN [FHAVN]), as well as its link to clinical and radiological outcomes, are poorly understood. Osteonecrosis, which results from a disruption in vascular supply to the femoral head, is a prevalent cause of hip joint deterioration and one of the most common reasons for total hip arthroplasty (THA)/total hip replacement in India and other Asian countries. This study will aid in understanding the condition’s epidemiology and statistically determining the risk of disease related with pandemic exposure. Materials and Methods: This is a retrospective study of 100 hips diagnosed with osteonecrosis/osteoarthritis of the femoral head that underwent THA at a tertiary care center before and after the COVID-19 pandemic between February 2014 and February 2024. Results: Late stages of FHAVN, when the diagnosis requiring THA, following the pandemic have increased exponentially. It has also switched from affecting the middle-aged to the younger age groups. Furthermore, the bilaterality necessitating THA has increased considerably. There is a clear shift in the presentation of this disabling illness, as well as the need for THA, which otherwise is rarely carried out on younger people. Furthermore, data on how much corticosteroids were used in the treatment is disturbingly scant, and how it may have contributed to this ailment in India is still questionable. Conclusion: The COVID-19 pandemic could be the most serious threat, causing late-stages FHAVN (stages 3 and 4 of the Ficat and Arlet classification), in an accelerated manner, necessitating THA and overburdening existing medical care.